Methods for Teaching Literacy to Early Elementary English Learners - Gilbert, Brianna (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2023)
This paper focuses on the need for current and pre-service educators to learn how to effectively use instructional strategies to teach literacy to English learners. Research centers on methods that target the emergent literacy skills of English learners enrolled in kindergarten through grade three. Currently, data demonstrates that English learners are entering American public schools at an increasing rate. Early elementary educators are the first teachers that will encounter the new influx of these students. The following information examines two methods that early elementary educators can use to instruct English learners effectively and improve their language and literacy capabilities. English learners require strong emergent literacy skills to find academic success as they ascend grade levels and encounter more advanced texts.